Determinan Nilai Perusahaan Ditinjau dari Struktur Modal, Kemampuan Laba dan Kebijakan Dividen - Ratih Tri Wulansari; Agus Budi Santosa (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2018)
This study aims to to analyze factors affecting value of firms.Variables used in this research was capital structure , the ability profit, and policies dividends. Population in this research is companies index LQ 45 listed on the indonesian stock in the period research 2013-2015 year. Sample in research this is a company manufacturing or services.Technique the sample collection use purposive sampling. Technique analysis the data used was regression analysis linear multiple. The research results show only variable the ability the profit influential posistif significant impact on value of firm. While variable capital structure and policies dividends has not been affecting the value of enterprise